Research on torque feedback equivalent structures in the multi‐layer and multi‐axis synchronisation control model - Jie Xu; Sizhou Sun; Huacai Lu (IET Circuits, Devices and Systems)
Abstract This paper proposes a novel torque feedback equivalent structure oriented to the diversity of torque feedback in multi‐layer and multi‐axis complex systems. First, in view of the existing synchronisation control problem, this paper presents master reference synchronous model and master–slave synchronous model in a multi‐layer and multi‐axis synchronous control system. Second, the change of the direct feedback to front layer axis is lower than that of the direct feedback to master axis, and the adjustment difference of the axis output is low. Moreover, the stability and superiority of the proposed controller are theoretically analysed. By two methods, it can be seen that the control system can converge at a faster speed and run stably with good dynamic performance and synchronisation performance. The results verify the effectiveness of the adaptive control model in which the two equivalent torque feedback structures converge to zero.